2021
DOI: 10.1080/10447318.2021.1898827
|View full text |Cite
|
Sign up to set email alerts
|

ViBreathe: Heart Rate Variability Enhanced Respiration Training for Workaday Stress Management via an Eyes-Free Tangible Interface

Abstract: Slow breathing guiding applications increasingly emerge, showing promise for helping knowledge workers to better cope with workaday stress. However, standard breathing guidance is non-interactive, with rigid paces. Despite their effects being proved, they could cause respiratory fatigue, or lack of training motivation, especially for novice users. To explore new design possibilities, we investigate using heart rate variability (HRV) data to mediate breathing guidance, which results in two HRV-enhanced guidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 60 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…For the ASMR sound sources we found on YouTube, it is judged that a sound masking effect was created because the frequency characteristic with time has the characteristics of intermittent white or pink noise. In addition, research shows that listening to the sounds of nature can affect the body to calm and relax [ 75 ]. Therefore, the sounds of nature, including the sound of rain, create a calm atmosphere for meditation and, as a result, induce sleep by relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…For the ASMR sound sources we found on YouTube, it is judged that a sound masking effect was created because the frequency characteristic with time has the characteristics of intermittent white or pink noise. In addition, research shows that listening to the sounds of nature can affect the body to calm and relax [ 75 ]. Therefore, the sounds of nature, including the sound of rain, create a calm atmosphere for meditation and, as a result, induce sleep by relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…The method can be respiratory by regulating breathing activities or muscles. Regularity in breathing, especially with the right rhythm, will cause the mental attitude and body to relax (Yu et al, 2021). From the explanation above, it can be concluded that relaxation is a state where individuals feel calm, comfortable, and peaceful.…”
Section: Spiritual Relaxation Therapymentioning
confidence: 99%